2018
DOI: 10.1136/bmjopen-2017-020692
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effect of SGLT-2 inhibitors on microvascular outcomes in patients with type 2 diabetes: a review protocol

Abstract: IntroductionSodium glucose cotransporter 2 (SGLT-2) inhibitors are a relatively new drug-class of glucose-lowering medications. Several trials and systematic reviews have demonstrated their beneficial effect on some macrovascular outcomes. Their effect on microvascular outcomes has been reported as positive in several trials, however, their effect remains uncertain. Therefore, we report the protocol of a systematic review and meta-analysis aimed at determining the effect of SGLT-2 inhibitors regarding patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Clinical studies found that BP parameters were lower than baseline 6 weeks after Dagliazine treatment. Therefore, Dagliazine may prevent retinal wall remodeling by lowering BP [ 34 ].…”
Section: The Treatment Of New Diabetic Drug Sglt2 Inhibitor On Thementioning
confidence: 99%
“…Clinical studies found that BP parameters were lower than baseline 6 weeks after Dagliazine treatment. Therefore, Dagliazine may prevent retinal wall remodeling by lowering BP [ 34 ].…”
Section: The Treatment Of New Diabetic Drug Sglt2 Inhibitor On Thementioning
confidence: 99%